2015
DOI: 10.9755/ejfa.2015.04.101
|View full text |Cite
|
Sign up to set email alerts
|

Plasma profile of progesterone, estradiol-17beta and some blood biochemical attributes during different gestation periods in Iraqi female dromedary camels (Camelus dromedarius)

Abstract: This study was conducted to demonstrate the plasma profile of progesterone, estradiol-17β and some blood biochemical attributes (glucose, cholesterol concentrations and alkaline phosphates activity) of Iraqi female dromedary camels (Camelus dromedarius) during different gestation periods. This experiment included 5 multiparous, non-lactating Iraqi one-humped female camels (Camelus dromedarius) of 7-8 years old. Blood was collected from female camels at days 20, 30, 40, 50, 60, 90, 120,. The plasma progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Reports of the study of Muhammad et al (2011) showed the comparison of non-pregnant to pregnant camels and was not found significant differences; 19.8 vs 27.03 pg/ml, respectively. Tibary and Anouassi (1997) reported estradiol concentrations increased after fecundation and showed irregular differences during the first two trimesters of pregnancy and Abdulkareem et al (2015) reported its value ranged between 34.5 and 45.8 pg/ml. Mean concentrations of estradiol reported by Cristofori and Quaranta (1993) as its level was 60.0±5.4 pg/ml during the 1 st trimester of pregnancy, 71±9.0 pg/ ml level was during 2 nd trimester, and 95±3.3 pg/ml values during 3 rd trimester.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of the study of Muhammad et al (2011) showed the comparison of non-pregnant to pregnant camels and was not found significant differences; 19.8 vs 27.03 pg/ml, respectively. Tibary and Anouassi (1997) reported estradiol concentrations increased after fecundation and showed irregular differences during the first two trimesters of pregnancy and Abdulkareem et al (2015) reported its value ranged between 34.5 and 45.8 pg/ml. Mean concentrations of estradiol reported by Cristofori and Quaranta (1993) as its level was 60.0±5.4 pg/ml during the 1 st trimester of pregnancy, 71±9.0 pg/ ml level was during 2 nd trimester, and 95±3.3 pg/ml values during 3 rd trimester.…”
Section: Resultsmentioning
confidence: 99%